UNA APUESTA POLÍTICA DESDE LAS MUJERES POR LA LUCHA DE LA VIVIENDA - Arroyo Araya, Helga (2018)
This article analyses the link that people from popular sectors and organized groups around housing issues, and perceived as “needed subjects” establishes with State institutions, NGOs, private sector and churches. Popular organization is here examined through feminism perspective of women and participative methodologies. Furthermore, the perspective of women that organized themselves on 2016 were also helpful to elaborate critical thoughts that try to produce more liberating political proposals.